2019
DOI: 10.1097/mlr.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Patient Experience Data Collection Processes for Lower Literacy Patient Populations Using Tablets at the Point of Care

Abstract: Background: Patient experience surveys are widely used to capture patient-reported quality of care and are increasingly being used for formal reporting purposes. There is evidence that certain patient subgroups are less likely to respond to traditional CAHPS surveys. As patient-facing technologies become more common, it is important to examine whether tablet-based patient experience surveys have the potential to promote responses from more diverse populations. Objectives: To develop, gain perspectives about, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This may be mainly due to our face-to-face mode for data collection, which usually gains higher response rates than mail or telephone approaches. In addition, we believe that the electronic questionnaire and online survey system helped improve the participation of hard-to-reach groups in our trial, as demonstrated by the similar tablet administration in Japan and the US (18)(19)(20).…”
Section: Discussionmentioning
confidence: 88%
“…This may be mainly due to our face-to-face mode for data collection, which usually gains higher response rates than mail or telephone approaches. In addition, we believe that the electronic questionnaire and online survey system helped improve the participation of hard-to-reach groups in our trial, as demonstrated by the similar tablet administration in Japan and the US (18)(19)(20).…”
Section: Discussionmentioning
confidence: 88%